2013
DOI: 10.1128/jvi.01317-13
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteins gE and gI Are Required for Efficient KIF1A-Dependent Anterograde Axonal Transport of Alphaherpesvirus Particles in Neurons

Abstract: Alphaherpesviruses, including pseudorabies virus (PRV), spread directionally within the nervous systems of their mammalian hosts. Three viral membrane proteins are required for efficient anterograde-directed spread of infection in neurons, including Us9 and a heterodimer composed of the glycoproteins gE and gI. We previously demonstrated that the kinesin-3 motor KIF1A mediates anterograde-directed transport of viral particles in axons of cultured peripheral nervous system (PNS) neurons. The PRV Us9 protein cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 53 publications
3
91
0
Order By: Relevance
“…In addition, the role of the pUS9 acidic domain remains to be established precisely, given that this domain has been shown to be important for anterograde spread in a number of alphaherpesviruses (18)(19)(20). Finally, whether, and to what degree, the interaction of kinesin-3 and pUS9 identified in PrV (15,16) also is important for anterograde spread of HSV-1 requires further elucidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the role of the pUS9 acidic domain remains to be established precisely, given that this domain has been shown to be important for anterograde spread in a number of alphaherpesviruses (18)(19)(20). Finally, whether, and to what degree, the interaction of kinesin-3 and pUS9 identified in PrV (15,16) also is important for anterograde spread of HSV-1 requires further elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of PrV pUS9 with kinesin-3 depends on the presence of the additional viral glycoproteins gE and gI (16). Phosphorylation of PrV pUS9, although not essential, does enhance the interaction with kinesin-3 (17).…”
mentioning
confidence: 99%
“…PRV gE/gI deletion viruses are also impaired in anterograde spread in rat models of retinal infection, despite no impairment of retrograde transport or replication within retinal ganglion neurons (14,15). Similarly, deletion of the PRV gI gene results in impairment of anterograde spread by compartmentalized chamber systems (16,17). However, VZV interactions within neuronal axons have been poorly defined to date due to the high human specificity of the virus, which places limitations on the models available to assess VZV neuronal infection (1,18).…”
mentioning
confidence: 99%
“…The heterodimer of the products of these genes play important role in cell-to-cell spreading of the virus and other connected functions (Snyder et al 2008;Kratchmarov et al 2013;Howard et al 2014;D C Johnson et al 2001). However we were interested in its part in viral gene expression, an area not well documented.…”
Section: Discussionmentioning
confidence: 99%
“…The us7 and us8 genes are preserved across alpha herpes viruses and various functions have been attributed to them, for example: binding to Fc receptors at mucosal surfaces (Knapp et al 1997) or sorting virion particles to cell junctions (David C Johnson et al 2001), as well as promoting anterograde spreading between neurons (Husak et al 2000). It has also been shown that both proteins are essential in axonal transport (Kratchmarov et al 2013) of the virus. Even though DNA replication of the virus is not affected in US7/US8 mutant viruses, their ability of cell-to-cell spreading and virion formation is impaired, thus the mutant viruses are attenuated (Snyder et 6.…”
Section: Viral Life Cyclementioning
confidence: 99%